ANALISIS DAN DESAIN LOCATION BASED SERVICE PADA JURUSAN TEKNIK INFORMATIKA FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA - Viktor Handrianus Pranatawijaya; Agus Sehatman Saragih (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
Room location search can be done by looking at the sign of the room. Along with the developmentof information technology services (IT) then to perform the above can be done by using the services of aLocation Based Service (LBS). The search of information and the location of Department of InformationEngineering, Faculty of Engineering UNPAR by using a mobile device can be done by using LBS servicesso that the necessary information can be viewed by the room. LBS at the Department of InformaticsEngineering, Faculty of Engineering UNPAR intended for information about lectures, lab work and areminder for the user can be obtained.The study was made of three phases: (1) data collection and analysis is done by means ofliterature study and observation, (2) applying the waterfall method which has been modified with thestages is a system analysis to determine access rights along with existing facilities, UML and ERD aremade, the design of the system by doing database design, navigation structure, interface, and (3) theresults of research in which document analysis and design for LBS can be made the basis for the softwareto implement.LBS at the Department of Informatics Engineering, Faculty of Engineering UNPAR generallyhave three users, namely: (1) the admin to manage point and information point, the user, the schedule oflectures and lab work, (2) a registered user to see the point and information point, managing the scheduleof lectures and practicum user, check in at the point, manage appointments, and provide notifications andreminders, and (3) the user is not registered to see the point and the point information and to register onthe system.